Aerosol type foam temporary coloring composition
The aerosol-type foam temporary colorant composition addresses stickiness and flaking issues by using specific surfactants and resins, providing a natural finish with improved water resistance and foam retention for even application.
Patent Information
- Application Number
- JP2020134923
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-07
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-08-07
AI Technical Summary
Existing aerosol-type temporary hair coloring compositions suffer from issues such as stickiness, flaking, poor water resistance, and uneven application, leading to an unnatural finish and difficulty in use.
An aerosol-type foam temporary colorant composition comprising polyoxyethylene alkyl ether nonionic surfactant, acrylic resin alkanolamine, nonionic film-forming resin, alkyl acrylate copolymer emulsion, coloring agent, and propellant, which is discharged as a foam to provide improved foam retention, water resistance, and abrasion resistance.
The composition achieves a natural finish without stickiness or flaking, with good coloring properties, water resistance, and effective foam retention, ensuring even application and reduced contamination.
Smart Images

Figure 0007618196000001 
Figure 0007618196000002 
Figure 0007618196000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an aerosol type temporary foam colorant composition, and more particularly to an aerosol type temporary foam colorant composition which is free from flaking and stickiness and has good coloring properties, water resistance, abrasion resistance and foam retention. [Background technology]
[0002] In recent years, there has been an increasing demand for products that allow users to change hair color simply and easily without complicated operations. Among these, temporary hair coloring compositions that allow users to easily change hair color tone have attracted attention.
[0003] Temporary hair coloring compositions generally color hair by attaching a coloring agent such as a pigment or organic dye to the hair. Compared to so-called oxidation hair dyes, which utilize a chemical reaction (oxidative polymerization) using an oxidation dye and an oxidizing agent, they cause little damage to hair and can be washed off in one wash, making them widely used. Among these, aerosol-type temporary hair coloring agents, which use a propellant, are easy to apply over a wide area and are easy to use, so there is a growing demand in the market.
[0004] Conventionally, some aerosol temporary colorants have used anionic film-forming agents or polymeric thickeners to fix the colorant on the hair in order to improve abrasion resistance and water resistance after drying (Patent Document 1).
[0005] Furthermore, a color hair cosmetic containing an amphoteric polymer resin, an acid dye, and a pigment has been disclosed as a cosmetic that has high coloring properties on hair but causes little secondary adhesion (Patent Document 2).
[0006] Furthermore, as a type of aerosol temporary coloring agent, a coloring material-containing aerosol cosmetic that is sprayed in mist form using a spray nozzle has been disclosed (Patent Document 3). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Laid-Open No. 2003-26553 [Patent Document 2] Japanese Patent Application Publication No. 11-124319 [Patent Document 3] Japanese Patent Application Laid-Open No. 2003-81762 Summary of the Invention [Problem to be solved by the invention]
[0008] However, in Patent Document 1, when an aerosol temporary hair colorant composition is applied to hair, the anionic film-forming agent and polymer thickener that are blended for the purpose of improving friction resistance and water resistance after drying not only fix the colorant to the hair but also cause the hair strands to stick together, making the hair stiff and forming thick clumps, resulting in an unnatural finish that is stiff and unnatural, and making the hair sticky, making it difficult to run your fingers through and feel.
[0009] Furthermore, although Patent Document 2 achieves both high coloring properties on hair and suppression of secondary adhesion, it does not pay attention to the degree of stickiness or flaking of the hair at the time of finishing, and there is still room for improvement in terms of achieving a natural finish without stickiness or flaking.
[0010] Furthermore, as in Patent Document 3, a method is known in which a spray-type aerosol cosmetic containing a coloring material, which is a type of aerosol temporary coloring agent composition, is sprayed in mist form; however, since the mist is sprayed over a wide area, it is difficult to apply the cosmetic uniformly to the hair, and the concentrate may adhere to unintended areas, resulting in contamination of the surrounding area. [Means for solving the problem]
[0011] As a result of intensive research by the present inventors to solve the above-mentioned problems, they have found that an aerosol-type temporary foam colorant composition can be obtained that is discharged in foam form (foam) from an aerosol container, the aerosol-type temporary foam colorant composition containing (A) a polyoxyethylene alkyl ether-type nonionic surfactant, (B) an acrylic resin alkanolamine, (C) a nonionic film-forming resin, (D) an alkyl acrylate copolymer emulsion, (E) an aerosol concentrate containing a colorant, and (F) a propellant, and have thus completed the present invention. [Effects of the Invention]
[0012] According to the present invention, an aerosol type temporary foam colorant composition can be obtained which is free from flaking and stickiness, and has good coloring properties, water resistance, abrasion resistance, and foam retention. DETAILED DESCRIPTION OF THE INVENTION
[0013] The present invention will be described in detail below. Note that the units indicating the contents are all % by mass unless otherwise specified.
[0014] Flaking in the present invention refers to the peeling off of the film-forming resin attached to the hair and the falling off of the colorant fixed to the hair by the formed film together with the film-forming resin, and means that the hair whose color tone has been changed by the aerosol foam temporary colorant composition becomes exposed.
[0015] The aerosol foam temporary colorant composition of the present invention comprises an aerosol concentrate and a propellant.
[0016] The aerosol concentrate of the present invention contains (A) a polyoxyethylene alkyl ether type nonionic surfactant from the viewpoint of foam retention.
[0017] The component (A) used in the present invention is not particularly limited, and examples thereof include polyoxyethylene (hereinafter referred to as POE) (2) lauryl ether (HLB: 9.5), POE (4) lauryl ether (HLB: 11.5), POE (9) lauryl ether (HLB: 14.5), POE (21) lauryl ether (HLB: 19.0), POE (25) lauryl ether (HLB: 19.5), POE (2) cetyl ether (HLB: 8.0), POE (6) cetyl ether (HLB: 10.5), POE (7) cetyl ether (HLB: 11.5), POE (8 ... ) Cetyl ether (HLB: 11.5), POE (10) cetyl ether (HLB: 13.5), POE (15) cetyl ether (HLB: 15.5), POE (20) cetyl ether (HLB: 17.0), POE (23) cetyl ether (HLB: 18.0), POE (25) cetyl ether (HLB: 18.5), POE (30) cetyl ether (HLB: 19.5), POE (40) cetyl ether (HLB: 20.0), POE (2) stearyl ether (HLB: 8.0), POE (4) stearyl ether POE (20) stearyl ether (HLB: 18.0), POE (2) oleyl ether (HLB: 7.5), POE (7) oleyl ether (HLB: 10.5), POE (10) oleyl ether (HLB: 14.5), POE (15) oleyl ether (HLB: 16.0), POE (20) oleyl ether (HLB: 17.0), POE (50) oleyl ether (HLB: 18.0), POE (5) behenyl ether (HLB: 7.0), POE (10) behenyl ether POE(20) behenyl ether (HLB: 16.5), POE(30) behenyl ether (HLB: 18.0), POE(3) alkyl(12-14) ether (HLB: 8.0), POE(5) alkyl(12-14) ether (HLB: 10.5), POE(7) alkyl(12-14) ether (HLB: 12.0), POE(9) alkyl(12-14) ether (HLB: 13.5), POE(12) alkyl(12-14) ether (HLB: 14.5), etc.Among them, from the viewpoint of forming foam when discharged from an aerosol container, POE (2) lauryl ether (HLB: 9.5), POE (4) lauryl ether (HLB: 11.5), POE (9) lauryl ether (HLB: 14.5), POE (21) lauryl ether (HLB: 19.0), POE (25) lauryl ether (HLB: 19.5), POE (2) cetyl ether (HLB: 8.0), POE (6 ... Cetyl ether (HLB: 10.5), POE (7) cetyl ether (HLB: 11.5), POE (10) cetyl ether (HLB: 13.5), POE (15) cetyl ether (HLB: 15.5), POE (20) cetyl ether (HLB: 17.0), POE (23) cetyl ether (HLB: 18.0), POE (25) cetyl ether (HLB: 18.5), POE (30) cetyl ether (HLB: 19.5), P POE(40) cetyl ether (HLB: 20.0), POE(3) alkyl(12-14) ether (HLB: 8.0), POE(5) alkyl(12-14) ether (HLB: 10.5), POE(7) alkyl(12-14) ether (HLB: 12.0), POE(9) alkyl(12-14) ether (HLB: 13.5), POE(12) alkyl(12-14) ether (HLB: 14.5) are preferred, and POE (3) alkyl (12-14) ether (HLB: 8.0), POE (12) alkyl (12-14) ether (HLB: 14.5), POE (2) cetyl ether (HLB: 8.0), POE (40) cetyl ether (HLB: 20.0), POE (4) lauryl ether (HLB: 11.5), POE (9) lauryl ether (HLB: 14.5), and POE (25) lauryl ether (HLB: 19.5) are more preferred. The component (A) may contain one or more types.
[0018] "HLB" is an abbreviation for Hydrophile-Lipophile Balance, and is generally a parameter that indicates the relative strength of the hydrophilic and lipophilic properties of a surfactant molecule; the higher the HLB value, the stronger the hydrophilicity, and the lower the HLB value, the stronger the lipophilicity. The HLB values described in this invention are based on actual measurements. The measurement method used was the method described in "Handbook - Cosmetics and Pharmaceutical Ingredients - Revised Edition, Nikko Chemicals Co., Ltd., 1977, pp. 854-855."
[0019] The content of the component (A) used in the present invention is preferably 0.5 to 3%, more preferably 0.6 to 2%, and even more preferably 0.8 to 1.5%. If the component (A) is less than 0.5%, the foam may not retain its foamability. If the component (A) is more than 3%, the foam may become sticky.
[0020] The average HLB of the component (A) used in the present invention is preferably at least 8.5, and more preferably at least 10. If the average HLB of the component (A) is less than 8.5, the foam may have reduced foam retention.
[0021] The aerosol concentrate of the present invention contains (B) an acrylic resin alkanolamine from the viewpoint of water resistance and abrasion resistance.
[0022] The component (B) used in the present invention is an acrylic resin neutralized with aminomethylpropanol (hereinafter referred to as AMP), aminomethylpropanediol (AMPD), triethanolamine (TEA), or the like. The component (B) is not particularly limited, but examples include (acrylates / diacetoneacrylamide) copolymer AMP, acrylates copolymer AMP, and (acrylates / alkyl(C1-18) acrylate / alkyl(C1-8)acrylamide) copolymer AMP. Among these, (acrylates / diacetoneacrylamide) copolymer AMP and (acrylates / alkyl(C1-18) acrylate / alkyl(C1-8)acrylamide) copolymer AMP are preferred from the viewpoints of water resistance and abrasion resistance, and (acrylates / diacetoneacrylamide) copolymer AMP is even more preferred from the viewpoint of flaking prevention. The component (B) may contain one or more types.
[0023] The content of the component (B) used in the present invention is preferably 0.1 to 5%, more preferably 0.5 to 2.5%, and even more preferably 0.7 to 2%. If the content of the component (B) is less than 0.1%, water resistance and abrasion resistance may decrease. If the content of the component (B) is more than 5%, flaking and stickiness may occur.
[0024] The aerosol concentrate of the present invention contains (C) a nonionic film-forming resin from the viewpoint of suppressing flaking.
[0025] The component (C) used in the present invention is not particularly limited, but examples include (dimethylacrylamide / hydroxyethyl acrylate / methoxyethyl acrylate) copolymer, (hydroxyethyl acrylate / methoxyethyl acrylate) copolymer, (hydroxyethyl acrylate / butyl acrylate / methoxyethyl acrylate) copolymer, vinyl acetate-vinylpyrrolidone copolymer ((vinylpyrrolidone / VA) copolymer), polyvinylpyrrolidone, vinyl methyl ether-ethyl maleate copolymer, (vinylpyrrolidone / methacrylamide / vinylimidazole) copolymer, and polyvinyl alcohol. Among these, (dimethylacrylamide / hydroxyethyl acrylate / methoxyethyl acrylate) copolymer, (hydroxyethyl acrylate / methoxyethyl acrylate) copolymer, and (hydroxyethyl acrylate / butyl acrylate / methoxyethyl acrylate) copolymer are preferred from the viewpoint of suppressing flaking, and (hydroxyethyl acrylate / methoxyethyl acrylate) copolymer is even more preferred from the viewpoint of achieving a natural finish after use. The component (C) may contain one or more types.
[0026] The content of the component (C) used in the present invention is preferably 0.05 to 5%, more preferably 0.1 to 2%, and even more preferably 0.2 to 1%. If the content of the component (C) is less than 0.05%, flaking may occur. If the content of the component (C) is more than 5%, stickiness may occur.
[0027] The aerosol concentrate of the present invention contains (D) an alkyl acrylate copolymer emulsion from the viewpoint of water resistance and abrasion resistance.
[0028] The component (D) used in the present invention is not particularly limited, but examples thereof include acrylate copolymer, ammonium acrylate copolymer, sodium acrylate copolymer, and ammonium (styrene / alkyl acrylate) copolymer, and ammonium acrylate copolymer is preferred from the viewpoint of suppressing flaking. The component (D) may contain one or more types.
[0029] The content of the component (D) used in the present invention is preferably 0.1 to 5%, more preferably 0.5 to 4%, and even more preferably 1 to 3%. If the content of the component (D) is less than 0.1%, water resistance and abrasion resistance may decrease. If the content of the component (D) is more than 5%, flaking and stickiness may occur.
[0030] The aerosol concentrate of the present invention contains a colorant (E) from the viewpoint of coloring properties.
[0031] The component (E) used in the present invention is not particularly limited, but examples thereof include inorganic pigments, pearl pigments, organic pigments, dye-resin solid solutions, daylight fluorescent pigments, and natural pigments. One or more types of component (E) may be contained. When two or more types of component (E) are contained, it is possible to create a variety of color tones.
[0032] Specific examples of the inorganic pigment include ultramarine, chromium oxide, red iron oxide, yellow iron oxide, titanium oxide, aluminum hydroxide, zinc oxide, cobalt oxide, black iron oxide, chromium hydroxide, aluminum hydroxide, Prussian blue, barium sulfate, hydrous silicate, silicic acid anhydride, aluminum silicate, mica, magnesium carbonate, manganese violet, carbon black, aluminum, copper, gold, etc. One or more of these inorganic pigments may be contained.
[0033] Specific examples of the pearl pigment include combinations of titanium oxide / iron oxide / mica, titanium oxide / ferrous metal / mica, red iron oxide / mica, synthetic phlogopite / iron oxide, alumina / silica / iron oxide, and synthetic phlogopite / titanium oxide / tin oxide / iron oxide composite powders. Generic names for these composite powders include titanium mica, red iron oxide-coated mica, red iron oxide-coated mica titanium, black iron oxide-coated mica titanium, and chromium oxide-coated mica. One or more of these pearl pigments may be contained.
[0034] Specific examples of the organic pigment include Red No. 202, Red No. 203, Red No. 204, Red No. 205, Red No. 206, Red No. 207, Red No. 208, Red No. 219, Red No. 220, Red No. 221, Red No. 228, Red No. 404, Red No. 405, Orange No. 203, Orange No. 204, Orange No. 401, Yellow No. 205, Yellow No. 401, Blue No. 404, Red No. 104 Aluminum Lake, Yellow No. 4 Aluminum Lake, Yellow No. 203 Aluminum Lake, Blue No. 1 Aluminum Lake, etc. One or more of these organic pigments may be contained.
[0035] Specific examples of the natural pigment include mineral pigments such as clay, natural dye lakes such as madder lake and cochineal lake, azo pigments, phthalocyanine pigments, etc. One or more of these natural pigments may be contained.
[0036] Among the above colorants, inorganic pigments, organic pigments and pearl pigments are preferred from the viewpoint of good color development on hair.
[0037] When the component (E) used in the present invention is an organic pigment or an inorganic pigment, the content is preferably 0.1 to 1%, more preferably 0.2 to 0.8%. If the component (E) is less than 0.1%, coloring properties may be reduced. If the component (E) is more than 1%, flaking may occur and abrasion resistance may be reduced.
[0038] When the component (E) used in the present invention is a pearl pigment, its content is preferably 1 to 10%, more preferably 3 to 8%. If the content of the pearl pigment (E) is less than 1%, coloring properties may be reduced. If the content of the pearl pigment (E) is more than 10%, flaking may occur and abrasion resistance may be reduced.
[0039] The present invention contains a propellant (F) from the viewpoint of discharging the composition in the form of foam from an aerosol container.
[0040] The component (F) used in the present invention is not particularly limited, but examples thereof include dimethyl ether (DME), isobutane, liquefied petroleum gas (LPG), and nitrogen gas. Among these, liquefied petroleum gas or dimethyl ether is preferred from the viewpoint of preventing clogging, and liquefied petroleum gas is more preferred from the viewpoint of good dischargeability. The component (E) may contain one or more kinds.
[0041] The component (F) used in the present invention preferably has an initial internal pressure in the range of 0.2 to 0.5 MPa at 20° C. The initial internal pressure can be adjusted to any desired value by changing the composition of the liquefied petroleum gas, and can also be adjusted by combining the liquefied petroleum gas with a type of dimethyl ether, etc.
[0042] From the viewpoint of good dischargeability, the mass ratio of the aerosol concentrate used in the present invention to the component (F) (aerosol concentrate:propellant) is preferably 97:3 to 80:20, more preferably 96:4 to 90:10. If the mass ratio of the component (F) is less than 3, it may not be possible to discharge the concentrate in the form of foam from the aerosol container. If the mass ratio of the component (F) is more than 20, the concentrate may splash and contaminate the surrounding area.
[0043] In addition to the components (A) to (F), the aerosol foam temporary colorant composition of the present invention may contain at least one selected from various components commonly used in cosmetics, quasi-drugs, pharmaceuticals, etc., such as surfactants other than component (A), oily components, moisturizers, thickeners, medicinal ingredients, protein derivatives, hydrolyzed proteins, stabilizers, antioxidants, plant extracts, herbal extracts, vitamins, preservatives, colorants, pigments, powders, pH adjusters, UV absorbers, fragrances, etc., within a range that does not impair the effects of the present invention. However, the components are not limited to these examples.
[0044] The aerosol-type temporary foam colorant composition of the present invention can be used in an aerosol container made of metal, PET, or the like, depending on the application, purpose, method, environment of use, etc. The specifications of the aerosol container are not particularly limited, but examples of the container include pressure-resistant containers made of aluminum, tinplate, or plastic, the inside of which is coated with epoxyphenol or the like. Among these, aluminum is more preferred in terms of moldability and lightness. Furthermore, as the valve, a valve normally used for foaming is preferably used, and after the valve is attached and the propellant is filled, a foam spout (e.g., "FD147W"3": manufactured by Mitani Valve Co., Ltd.) is preferably attached.
[0045] The aerosol foam temporary colorant composition of the present invention can be applied to hair by brush or by hand, with application by brush being more preferred.
[0046] The aerosol type temporary colorant foam composition of the present invention may contain glass beads (12φ) for the purpose of dispersing colorants and the like. [Example]
[0047] The present invention will be described in more detail below with reference to examples, but these examples are not intended to limit the present invention in any way.
[0048] In the evaluation tests described herein, the components contained in the aerosol type foam temporary colorant composition and their contents were varied. The units showing the contents of each component are all % by mass, and these compositions were prepared by conventional methods.
[0049] <Evaluation> In the evaluation test method shown in this specification, the evaluation items were "non-flaking," "non-stickiness," "coloration," "water resistance," and "abrasion resistance," and the evaluation was carried out by 10 panelists, and the evaluation item was "foam retention" and the evaluation was carried out by one panelist.
[0050] In the invention described herein, in the evaluation tests for "freedom from flaking," "freedom from stickiness," "colorability," "water resistance," "abrasion resistance," and "foam retention," the obtained aerosol concentrate was filled into an aluminum can (manufactured by Takeuchi Press Kogyo Co., Ltd., outer diameter: 35 mm, total length: 100 mm, inner surface coating: TPL-419), two glass beads (12φ) were placed inside, an aerosol valve and a spout were installed, and then a propellant was added to prepare a 40 g aerosol-type foam temporary colorant composition, which was then evaluated.
[0051] <No flaking> At 25°C, 2 g of the obtained aerosol foam temporary colorant composition was dispensed onto the V-shaped straight brush attached to "Benezel Straight Perm EX (manufactured by Dariya Co., Ltd.)" and applied directly and uniformly to a portion of the hair of a hair test doll (100% human black hair, manufactured by Bealux Co., Ltd., model number: Queen Cut No. 775N). The hair was dried with a hair dryer while being combed for 5 minutes, and the state of removal of the applied product after combing 50 times using the V-shaped straight brush attached to "Benezel Straight Perm EX (manufactured by Dariya Co., Ltd.)" was visually evaluated according to the following criteria.
[0052] (Evaluation criteria) [Evaluation result]: [Score] Almost no peeling of the applied area: 5 points Slight peeling observed in the applied area: 4 points Peeling of the applied area is observed: 3 points The applied area peels off considerably: 2 points The applied area almost peels off: 1 point (Average score criteria) [Average score]: [Judgment] 4.5 or above: ◎ 3.0 or more and less than 4.5: ○ 1.5 or more and less than 3.0: △ Less than 1.5: ×
[0053] <Non-sticky> At 25°C, 2 g of the obtained aerosol foam temporary colorant composition was taken up in a V-shaped straight brush attached to "Benezel Straight Perm EX (manufactured by Dariya Co., Ltd.)" and applied directly and uniformly to a part of the hair of a hair test doll (100% human black hair, manufactured by Bealux Co., Ltd., model number: Queen Cut No. 775N). The doll was dried with a hair dryer while combing for 5 minutes, and the feel of the hair after it had cooled down was evaluated according to the following criteria.
[0054] (Evaluation criteria) [Evaluation result]: [Score] No stickiness at all: 5 points No stickiness: 4 points Almost no stickiness: 3 points Sticky: 2 points Very sticky: 1 point (Average score criteria) [Average score]: [Judgment] 4.5 or above: ◎ 3.0 or more and less than 4.5: ○ 1.5 or more and less than 3.0: △ Less than 1.5: ×
[0055] <Colorability> At 25°C, 2 g of the obtained aerosol foam temporary colorant composition was taken into a V-shaped straight brush attached to "Benezel Straight Perm EX (manufactured by Dariya Co., Ltd.)" and applied directly and uniformly to a part of the hair of a hair test doll (100% human black hair, manufactured by Bealux Co., Ltd., model number: Queen Cut No. 775N). The hair was combed for 5 minutes and then dried with a hair dryer, and the state of coverage of the hair was visually evaluated according to the following criteria.
[0056] (Evaluation criteria) [Evaluation result]: [Score] Very good coloring: 5 points Good coloring: 4 points Coloring is good: 3 points Slightly poor coloring: 2 points Poor coloring: 1 point (Average score criteria) [Average score]: [Judgment] 4.5 or above: ◎ 3.0 or more and less than 4.5: ○ 1.5 or more and less than 3.0: △ Less than 1.5: ×
[0057] <Water resistance> 0.25 g of the obtained aerosol foam temporary colorant composition was applied to 1 g of a 100% black hair bundle (product number: BS-BA, manufactured by Beaulux Co., Ltd.) at 25°C using a V-shaped straight brush attached to "Benezel Straight Perm EX (manufactured by Dariya Co., Ltd.)", and then the hair bundle was dried with a hair dryer while combing for 5 minutes. Warm water adjusted to 40°C was sprayed onto the hair bundle from a distance of 20 cm using a spray bottle, and the drops dripping from the hair bundle were collected in a lightweight standard glass bottle No. 5K, and the coloration of the warm water was evaluated visually according to the following criteria.
[0058] (Evaluation criteria) [Evaluation result]: [Score] No coloring in water: 5 points Slight discoloration in water: 4 points Coloring in water: 3 points Significant coloring in water: 2 points Very strong coloring in water: 1 point (Average score criteria) [Average score]: [Judgment] 4.5 or above: ◎ 3.0 or more and less than 4.5: ○ 1.5 or more and less than 3.0: △ Less than 1.5: ×
[0059] <Abrasion resistance> To 1 g of a 100% black hair bundle (product number: BS-BA, manufactured by Beaulux Co., Ltd.), 0.25 g of the obtained aerosol foam temporary colorant composition was applied using a V-shaped straight brush attached to a Benezel Straight Perm EX (manufactured by Dariya Co., Ltd.) at 25°C, and the hair was allowed to dry naturally for 24 hours. Next, the hair bundle was fixed to a horizontal stand, and a test white cloth (JIS L 0803 attached white cloth for color fastness test) wrapped around an 850 g weight was placed on the test hair bundle, rubbed three times, and color transfer was evaluated visually according to the following criteria.
[0060] (Evaluation criteria) [Evaluation result]: [Score] No transfer at all: 5 points Almost no transfer: 4 points Transfers seen: 3 points There is considerable variation: 2 points Very transferable: 1 point (Average score criteria) [Average score]: [Judgment] 4.5 or above: ◎ 3.0 or more and less than 4.5: ○ 1.5 or more and less than 3.0: △ Less than 1.5: ×
[0061] <Foam mochi> 2 g of the obtained aerosol type foam temporary colorant composition was discharged into a 300 mL tall beaker at 25°C and left to stand for 10 minutes, after which the appearance of the foam remaining in the 300 mL tall beaker was visually evaluated according to the following criteria.
[0062] (Evaluation criteria) [Evaluation result]: [Judgment] More than 80% of the foam remains compared to the initial state: ◎ Compared to the initial state, between 50% and 80% of the foam remains: Yes Compared to the initial state, between 20% and 50% of the foam remains: △ Less than 20% of the foam remains compared to the initial state: ×
[0063] [Table 1]
[0064] Examples 1 to 12 shown in Table 1 showed no flaking or stickiness, and showed good results in colorability, water resistance, abrasion resistance and foam retention.
[0065] [Table 2]
[0066] Examples 13 to 20 shown in Table 2 showed no flaking or stickiness, and showed good results in colorability, water resistance, abrasion resistance and foam retention.
[0067] [Table 3]
[0068] Examples 21 to 30 shown in Table 3 showed no flaking or stickiness, and showed good results in colorability, water resistance, abrasion resistance and foam retention.
[0069] [Table 4]
[0070] Examples 31 to 40 shown in Table 4 showed no flaking or stickiness, and showed good results in colorability, water resistance, abrasion resistance and foam retention.
[0071] [Table 5]
[0072] Examples 41 to 50 shown in Table 5 showed no flaking or stickiness, and showed good results in colorability, water resistance, abrasion resistance and foam retention.
[0073] [Table 6]
[0074] Examples 51 to 57 shown in Table 6 showed no flaking or stickiness, and showed good results in colorability, water resistance, abrasion resistance and foam retention.
[0075] [Table 7]
[0076] Examples 58 to 66 shown in Table 7 showed no flaking or stickiness, and showed good results in colorability, water resistance, abrasion resistance and foam retention.
[0077] The aerosol type foam temporary colorant compositions obtained in the following Examples 67 to 70 were free from flaking and stickiness, and gave good results in terms of coloring properties, water resistance, abrasion resistance, and foam retention.
[0078] Example 67 Component Content (mass%) (A) POE(2) cetyl ether (HLB: 8.0) 0.20% (A) POE(40) cetyl ether (HLB: 20.0) 1.00% (B) (Acrylates / diacetone acrylamide) copolymer AMP 2.00% (C) (Hydroxyethyl acrylate / Methoxyethyl acrylate) Copolymer 0.40% (D) Ammonium acrylate copolymer 1.44% (E) Bengala 0.20% (E) Bengala / mica *3 4.80% (E) Synthetic phlogopite / iron oxide *4 1.60% Concentrated glycerin 0.20% Bentonite 1.50% Ethanol 10.00% Methyl parahydroxybenzoate 0.10% D-Pantothenyl alcohol 0.20% Polyoxyethylene coconut oil fatty acid glyceryl 0.60% Camellia oil 0.01% Fragrance 0.01% Highly polymerized methylpolysiloxane (1) 1.25% Purified water 74.49% Total 100.00% ------------------------------------------------------ The above aerosol concentrate (average HLB: 18.0) 95.00% Liquefied petroleum gas (20℃, 0.39MPa) 5.00% Total 100.00%
[0079] Example 68 Component Content (mass%) (A) POE(7) alkyl(12-14) ether (HLB: 12.0) 1.00% (B) (Acrylates / diacetone acrylamide) copolymer AMP 2.00% (C) (Hydroxyethyl acrylate / Methoxyethyl acrylate) Copolymer 0.40% (D) Ammonium acrylate copolymer 1.44% (E) Bengala 0.20% (E) Bengala / mica *3 3.20% (E) Synthetic phlogopite / iron oxide *4 3.20% Concentrated glycerin 0.20% Bentonite 1.50% Ethanol 10.00% Methyl parahydroxybenzoate 0.10% D-Pantothenyl alcohol 0.20% Polyoxyethylene coconut oil fatty acid glyceryl 0.60% Camellia oil 0.01% Fragrance 0.01% Highly polymerized methylpolysiloxane (1) 1.25% Purified water 74.69% Total 100.00% ---------------------------------------- The above aerosol concentrate 95.00% Liquefied petroleum gas (20℃, 0.39MPa) 5.00% Total 100.00%
[0080] Example 69 Component Content (mass%) (A) POE(4) Lauryl Ether (HLB: 11.5) 0.83% (A) POE(9) Lauryl Ether (HLB: 14.5) 0.17% (B) (Acrylates / diacetone acrylamide) copolymer AMP 2.00% (C) (Hydroxyethyl acrylate / Methoxyethyl acrylate) Copolymer 0.40% (D) Ammonium acrylate copolymer 1.44% (E) Bengala 0.20% (E) Bengala / mica *3 3.20% (E) Synthetic phlogopite / iron oxide *4 3.20% Concentrated glycerin 0.20% Bentonite 1.50% Ethanol 10.00% Methyl parahydroxybenzoate 0.10% D-Pantothenyl alcohol 0.20% Polyoxyethylene coconut oil fatty acid glyceryl 0.60% Camellia oil 0.01% Fragrance 0.01% Highly polymerized methylpolysiloxane (1) 1.25% Purified water 74.69% Total 100.00% ---------------------------------------- The above aerosol concentrate (average HLB: 12.0) 95.00% Liquefied petroleum gas (20℃, 0.39MPa) 5.00% Total 100.00%
[0081] Example 70 Component Content (mass%) (A) POE(4) Lauryl Ether (HLB: 11.5) 0.83% (A) POE(9) Lauryl Ether (HLB: 14.5) 0.17% (B) (Acrylates / diacetone acrylamide) copolymer AMP 2.00% (C) (Hydroxyethyl acrylate / Methoxyethyl acrylate) Copolymer 0.40% (D) Ammonium acrylate copolymer 1.44% (E) Bengala 0.20% (E) Bengala / mica *3 3.20% (E) Synthetic phlogopite / iron oxide *4 3.20% POE(10) Sodium Lauryl Ether Phosphate 0.50% Concentrated glycerin 0.20% Bentonite 1.50% Ethanol 10.00% Methyl parahydroxybenzoate 0.10% D-Pantothenyl alcohol 0.20% Polyoxyethylene coconut oil fatty acid glyceryl 0.60% Camellia oil 0.01% Fragrance 0.01% Highly polymerized methylpolysiloxane (1) 1.25% Purified water 74.19% Total 100.00% ---------------------------------------- The above aerosol concentrate (average HLB: 12.0) 95.00% Liquefied petroleum gas (20℃, 0.39MPa) 5.00% Total 100.00% [Industrial Applicability]
[0082] The present invention provides an aerosol type temporary foam colorant composition that is free from flaking and stickiness, and has good coloring properties, water resistance, abrasion resistance, and foam retention.
Claims
[Claim 1] An aerosol type foam temporary colorant composition which is discharged in a foam form from an aerosol container, (A) Polyoxyethylene alkyl ether type nonionic surfactant (B) (Acrylates / diacetoneacrylamide) copolymer AMP (C) (hydroxyethyl acrylate / methoxyethyl acrylate) copolymer (D) Ammonium acrylates copolymer (E) One or more pigments selected from organic pigments, inorganic pigments, and pearl pigments and (F) a propellant, An aerosol type foam temporary colorant composition, characterized in that the average HLB of the component (A) in the aerosol concentrate is 10 or more, the content of the component (A) is 0.8 to 1.5 mass%, the content of the component (B) is 0.7 to 2 mass%, the content of the component (C) is 0.2 to 1 mass%, the content of the component (D) is 1 to 3 mass%, the content of the component (E) is 0.2 to 0.8 mass% when the component (E) is an organic pigment or an inorganic pigment, and the content of the component (E) is 3 to 8 mass% when the component (E) is a pearl pigment, and the mass ratio of the aerosol concentrate to the component (F) is 96:4 to 80:20.
Citation Information
Patent Citations
Color hair cosmetic
JP1999124319A
Temporally hair-coloring agent composition of aerosol type
JP2003026553A
Aerosol cosmetic formulated with coloring material
JP2003081762A
Composition for hair spray
JP2012056848A
Discharge product
JP2012236775A